Management of primary hyperparathyroidism in pregnancy: a case series. (16th May 2019) - McCarthy, Aisling; Howarth, Sophie; Khoo, Serena; Hale, Julia; Oddy, Sue; Halsall, David; Fish, Brian; Mariathasan, Sashi; Andrews, Katrina; Oyibo, Samson O; Samyraju, Manjula; Gajewska-Knapik, Katarzyna; et al.
Summary: Primary hyperparathyroidism (PHPT) is characterised by the overproduction of parathyroid hormone (PTH) due to parathyroid hyperplasia, adenoma or carcinoma and results in hypercalcaemia and a raised or inappropriately normal PTH. Symptoms of hypercalcaemia occur in 20% of patients and include fatigue, nausea, constipation, depression, renal impairment and cardiac arrythmias. In the most severe cases, uraemia, coma or cardiac arrest can result. Primary hyperparathyroidism in pregnancy is rare, with a reported incidence of 1%. Maternal and fetal/neonatal complications are estimated to occur in 67 and 80% of untreated cases respectively. Maternal complications include nephrolithiasis, pancreatitis, hyperemesis gravidarum, pre-eclampsia and hypercalcemic crises. Fetal complications include intrauterine growth restriction; preterm delivery and a three to five-fold increased risk of miscarriage. There is a direct relationship between the degree of severity of hypercalcaemia and miscarriage risk, with miscarriage being more common in those patients with a serum calcium greater than 2.85 mmol/L. Neonatal complications include hypocalcemia. Herein, we present a case series of three women who were diagnosed with primary hyperparathyroidism in pregnancy. Case 1 was diagnosed with multiple endocrine neoplasia type 1 (MEN1) in pregnancy and required a bilateral neck exploration and subtotal parathyroidectomy in the second trimester of her pregnancy due to symptomatic severe hypercalcaemia. Both case 2 and case 3 were diagnosed with primary hyperparathyroidism due to a parathyroid adenoma and required a unilateral parathyroidectomy in the second trimester. This case series highlights the work-up and the tailored management approach to patients with primary hyperparathyroidism in pregnancy. Learning points: Primary hyperparathyroidism in pregnancy is associated with a high incidence of associated maternal fetal and neonatal complications directly proportionate to degree of maternal serum calcium levels. Parathyroidectomy is the definitive treatment for primary hyperparathyroidism in pregnancy and was used in the management of all three cases in this series. It is recommended when serum calcium is persistently greater than 2.75 mmol/L and or for the management of maternal or fetal complications of hypercalcaemia. Surgical management, when necessary is ideally performed in the second trimester. Primary hyperparathyroidism is genetically determined in 10% of cases, where the likelihood is increased in those under 40 years, where there is relevant family history and those with other related endocrinopathies. Genetic testing is a useful diagnostic adjunct and can guide treatment and management options for patients diagnosed with primary hyperparathyroidism in pregnancy, as described in case 1 in this series, who was diagnosed with MEN1 syndrome. Women of reproductive age with primary hyperparathyroidism need to be informed of the risks and complications associated with primary hyperparathyroidism in pregnancy and pregnancy should be deferred and or avoided until curative surgery has been performed and calcium levels have normalised.